2019
DOI: 10.1038/s41467-019-11947-7
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of human bone marrow and blood natural killer cells defined by single-cell transcriptome

Abstract: Natural killer (NK) cells are critical to both innate and adaptive immunity. However, the development and heterogeneity of human NK cells are yet to be fully defined. Using single-cell RNA-sequencing technology, here we identify distinct NK populations in human bone marrow and blood, including one population expressing higher levels of immediate early genes indicative of a homeostatic activation. Functionally matured NK cells with high expression of CX3CR1 , HAVCR2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
239
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(266 citation statements)
references
References 77 publications
(101 reference statements)
27
239
0
Order By: Relevance
“…However, transcriptomic profiles of NK cells are beginning to demonstrate a wide range of heterogeneity within NK cell populations. For example, one study utilized single cell RNA sequencing (scRNA seq) to determine transitional populations of NK cells within bone marrow and PB that exist between these two examples (269). Another group demonstrated that NK cells exhibit organ-specific transcriptional profiles (270).…”
Section: Omics Studies On Nk Cell Activationmentioning
confidence: 99%
“…However, transcriptomic profiles of NK cells are beginning to demonstrate a wide range of heterogeneity within NK cell populations. For example, one study utilized single cell RNA sequencing (scRNA seq) to determine transitional populations of NK cells within bone marrow and PB that exist between these two examples (269). Another group demonstrated that NK cells exhibit organ-specific transcriptional profiles (270).…”
Section: Omics Studies On Nk Cell Activationmentioning
confidence: 99%
“…Specifically, ALL NK cells mainly represented clusters 10 and 16 that matched granzyme K (GZMK) expressing immature CD56 bright and translational NK cells (gene set scores in Fig. 4e represent the NK subtypes from a scRNA-seq study [45]). In comparison, the majority of the normal BM NK cells represented the mature or terminal NK cells (cluster 0) that express granzyme B (GZMB) and perforin (PRF1).…”
Section: The E/r+ Bm Immune Microenvironment Has Low Abundance and Acmentioning
confidence: 99%
“…Top 5 genes per cluster based on test score were extracted. Scores for NK subtype gene sets from [45] were calculated with the score_genes-function using the top 20 genes per gene set sorted by log-fold change.…”
Section: Nk Cell Analysismentioning
confidence: 99%
“…We used the overlapping test implemented in the GeneOverlap R package (https://github.com/shenlab-sinai/geneoverlap) to assess the overlap of our NHP NK cell signature with published collections of gene sets and pathways (Chaussabel et al, 2008;Liberzon et al, 2011;Nakaya et al, 2011;Newman et al, 2015;Costanzo et al, 2018;Yang et al, 2019). All gene sets and pathways that were enriched with a false discovery (FDR) q value cut-off of 0.05 were selected and the overlapping genes between these significant signatures and our NK RMtsig were used to generate heatmaps and gene networks.…”
Section: Pathways Enrichment Analysesmentioning
confidence: 99%